Analyse d´une expérience de l´utilisation de Facebook en classe de FLE à l´Université de Sancti Spiritus, Cuba - Luis Eyén Reina Garcia (Recherches en didactique des langues et des cultures)
Learning a foreign language far from the communities speaking that language usually creates enormous difficulties of motivation and mastery, even for those students who learn a language with the intention of teaching it later on. Since social networks, of which Facebook is the most popular, are nowadays at the heart of interpersonal interaction and since they redefine, as it were, the daily habits of their users, we have recognized that the opportunity to read and interact online, not only in the foreign language but also with the culture, goes hand in hand with the principles of language didactics which promote a communicative approach to foreign language teaching. In this way learners will be able to meet in the language of their friends, which contributes to authenticity. The writing of this article will shed light on the possible uses of social networks and we show an example of the use of Facebook for learning French as a foreign language at the University of Sancti Spiritus “José Marti Pérez” in Cuba.